The MWA GLEAM 4 Jy sample; a new large, bright radio source sample at 151 MHz - Jackson, C.; Franzen, T.; Seymour, N.; White, S.; Murphy, T.; Sadler, E.; Callingham, J.; Hunstead, R.; Hughes, J.; Wall, J.; Bell, M.; Dwarakanath, K.; et al. (SPIE - Internatioal Society for Optocal Engineering, 2015)
This paper outlines how the new GaLactic and Extragalactic All-sky MWA Survey (GLEAM, Wayth et al. 2015), observed by the Murchison Widefield Array covering the frequency range 72 231 MHz, allows identification of a new large, complete, sample of more than 2000 bright extragalactic radio sources selected at 151 MHz. With a flux density limit of 4 Jy this sample is significantly larger than the canonical fully-complete sample, 3CRR (Laing, Riley & Longair 1983). In analysing this small bright subset of the GLEAM survey we are also providing a firstuser check of the GLEAM catalogue ahead of its public release (Hurley-Walker et al. in prep). Whilst significant work remains to fully characterise our new bright source sample, in time it will provide important constraints to evolutionary behaviour, across a wide redshift and intrinsic radio power range, as well as being highly complementary to results from targeted, small area surveys.